Curadoria memética: a newsletter do meme - LINDOSO, Vitor Hugo Guimarães (2023)
The present work seeks to present the meme Newsletter, here called Memeletter. The research in question was conducted with the purpose of making the figure of speech known as "meme" more accessible and available to a wider audience. The research that used digital curatorship to collect memes and consequently create the acquisthat compose the editions of the informative, also serves as a model to contextualize the tool that curatorial in its most diverse models has become. Through this and also exploratory research, Memeletter was created as a tool that assists the process of understanding the meme while raising questions about its understanding, by means of applied questionnaire results, it is also understood that by being constant and possessing a rapid flow of innovation, the path of the meme is not understood by some subjects, argument that reinforces the need for a digital healing about the trajectory of this language figure called Meme.